On the solvability of the boundary value problems for the elliptic equation of high order on a plane - Koshanov, B. D.; Soldatov, A.P. (Bulletin of the Karaganda University. Mathematics Series, 2018)
For the elliptic equation of 2l-th order with of constant (and only) real coefficients we consider boundary value problem of the normal derivatives ( kj -1) order, j = 1,...,l, where 1 ≤ k1 <... < kl ≤ 2l-1. When kj = j it moves into the Dirichlet problem, and when kj = j+1 it moves into the Neumann problem. In SHAPE \* MERGEFORMAT this paper, the study is carried out in space C 2l,µ ( D ). We found the condition for Fredholm solvability of this problem and computed the index of this problem.